FABRICATION OF COMPOSITE COPPER/FLY ASH FOAM WITH EGG YOLK AS FOAMING AGENT - Amir Arifin; Gunawan Gunawan; Surya Adi Chandra (Asosiasi Peneliti Sriwijaya, 2020)
Copper has been widely in many applications such as heat exchangers due to mechanical and physical properties. In this work, the composite foam was fabricated by powder metallurgy method with fly ash powder and egg yolk as a foaming agent and reinforcement, respectively. Mechanical properties of the specimen were characterize using a compaction test. Moreover, observation of the specimen was conducted using the measurement of shrinkage and porosity. The strength of the specimen was obtained in the range 1:1,25 is 0,26 MPa through compaction test. Porosity measurement revealed that maximum and minimum porosities are 88.79 % and 71.53%, respectively. Optical Microscope and Scanning Electron Microscopy observation size of the pores ranging from 21,63μm to 169,7μm. Moreover, some crystalline phase was observed using X-Ray Diffraction Test.